Evaluation of difference in central corneal thickness between premenopausal and postmenopausal women - Verma, Neharika; Gupta, Palak; Sharma, Ashok (International Journal of Research in Medical Sciences, 2023)
Background: Menopause is defined as permanent cessation of menses. By convention the diagnosis of menopause is not made until the individual has had 12 months of amenorrhoea. It is a physiological condition, and associated with changes in levels of sex hormones. Certain changes occur in the corneal tissue due to change in these hormones. The current study intended to study any change in central corneal thickness among women after menopause. CCT can cause false readings in IOP measurements and affect the diagnosis and monitoring of glaucoma. Methods: It is a prospective, cross sectional, observational, case control study conducted in Department of Ophthalmology, GMC, Jammu for a period of 6 months from October 2022 to March 2023. 54 eyes of 27 patients each for pre and postmenopausal women were taken. Central corneal thickness was measured using specular biomicroscopy. Results: The mean age of post-menopausal women was found to be 52±2 years and pre-menopausal women was found to be 48±3. The mean of group 1 was found to be 524±18.67 microns and the mean of group 2 was found to 558±20.83 microns Conclusions: The data presented in this study suggest that menopause cause decrease in central corneal thickness.